"Having the heart to be evaluated": The differential effects of fears of positive and negative evaluation on emotional and cardiovascular responses to social threat. (December 2015) - Weeks, Justin W.; Zoccola, Peggy M.
Highlights: Cardiovascular and affective responses to positive social threat examined. Fears of positive/negative evaluation predicted anxiety/negative affect increases. Fear of positive evaluation alone predicted heart rate increases. Results inform upon commonalities and distinctions between these two social fears. Abstract: Accumulating evidence supports fear of evaluation in general as important in social anxiety, including fear of positive evaluation (FPE) and fear of negative evaluation (FNE). The present study examined state responses to an impromptu speech task with a sample of 81 undergraduates. This study is the first to compare and contrast physiological responses associated with FPE and FNE, and to examine both FPE- and FNE-related changes in state anxiety/affect in response to perceived social evaluation during a speech . FPE uniquely predicted (relative to FNE/depression) increases in mean heart rate during the speech; in contrast, neither FNE nor depression related to changes in heart rate. Both FPE and FNE related uniquely to increases in negative affect and state anxiety during the speech. Furthermore, pre-speech state anxiety mediated the relationship between trait FPE and diminished positive affect during the speech. Implications for the theoretical conceptualization and treatment of social anxiety are discussed.